Interventional Pain Management for the Pediatric Cancer Patient: A Literature Review - Christina Le-Short; Kavya Katragadda; Neil Nagda; David Farris; Marianne Halphen Gelter (MDPI AG, 2022)
This literature review examines the use of interventional treatments for pain management in pediatric cancer patients. While interventional procedures may be effective in cancer pain management, these procedures are infrequently employed in pediatric cohorts. This underutilization of interventional procedures may be supported by a deficit in randomized, controlled studies and literature regarding their role in pediatric cancer populations. Particularly because literature on the efficacy of interventional treatments in adult populations may not directly translate to pediatric populations, more research about the role of interventional procedures in managing pediatric cancer pain is necessary for a strengthened understanding of pediatric cancer pain treatment.